Sikap Fujoshi Dewasa Awal terhadap Konten Fiksi Homoromantic pada Grup Chat Penggemar XX - Umi Anisatul Faizah; Idha Rahayu Ningsih; Asti Candrasasi Catur Putri (MUTIARA: Jurnal Ilmiah Multidisiplin Indonesia, 2026)
The phenomenon of increasing consumption of homoromantic fiction content among early adult women has given rise to the term Fujoshi, which is often directly associated with support for LGBT issues, although such an interpretation does not necessarily reflect individuals’ attitudes in a comprehensive manner. This study is grounded in the need to understand the attitudes of early adult Fujoshi in a more nuanced and non-simplistic way, particularly through the framework of attitude theory encompassing cognitive, affective, and conative dimensions. The research problem focuses on how Fujoshi aged 18-40 interpret, experience, and express their attitudes toward homoromantic fiction content and its relationship to social values and norms in real life. This study employed a descriptive qualitative approach using in-depth interviews with three Fujoshi informants who are members of the XX fan chat group. The findings indicate that social media and peer networks play a significant role in the process of becoming a Fujoshi, as well as in shaping relatively intensive and repetitive patterns of content consumption as a form of emotional entertainment. Cognitively, the informants recognize that homoromantic fiction is related to LGBT issues; however, at the affective level, their interest is primarily driven by the uniqueness of the narrative structure and character dynamics rather than by sexual orientation itself. In the conative dimension, most informants do not demonstrate a tendency to support LGBT practices in real life; some even hold conservative views and display critical awareness of the potential negative impacts of their hobby, which they perceive as not fully aligned with prevailing social norms. The study concludes that Fujoshi attitudes are complex, ambivalent, and highly contextual. The novelty of this research lies in revealing a clear differentiation between the consumption of homoromantic fiction as a form of symbolic entertainment and individuals’ value positions toward social reality, which are often normatively conflated in previous assumptions.